Comparison of bimetallic Co-Ru nanoparticles supported on highly porous activated carbonized polyacrylonitrile with monometallic ones in ethanol steam reforming. Issue 6 (December 2021) - Efimov, M.N.; Mironova, E.Yu.; Vasilev, A.A.; Muratov, D.G.; Zhilyaeva, N.A.; Ozkan, S.Zh.; Karpacheva, G.P.
Abstract: A method for simultaneous formation of mono- (Co, Ru) or bimetallic (Co-Ru) nanoparticles and a highly porous carbon support is proposed. The obtained IR-PAN-Co, IR-PAN-Ru and IR-PAN-Co-Ru samples based on pyrolyzed polyacrylonitrile are characterized by a specific surface area within the range of 1683–2174 m 2 g -1, which strongly depends on the nature of the metal used. It has been shown that the presence of cobalt leads to the graphitization of amorphous carbon and the formation of carbon shells around the mono- and bimetallic nanoparticles. The average size of metallic nanoparticles for all three samples ranged within 12–20 nm. The comparison of the samples revealed a dramatic advantage of the bimetallic catalyst in the ethanol steam reforming (ESR). The IR-PAN-Co-Ru sample has shown the highest hydrogen yield, which was 5.6 moles per mole of EtOH at 550 °C. To evaluate the stability of the catalysts, the catalytic test was carried out for 17 h after which no deactivation of the catalysts was observed. The spent catalysts were characterized by the same techniques as the as-prepared ones. It was found that there are no significant changes in the structure of the catalysts after the ESR reaction. The presence of filamentous carbon in the spent cobalt-based catalysts has been observed, which does not lead to deactivation in the time period studied. Graphical Abstract: ga1 Highlights: Simultaneous formation of porous carbon support and metal nanoparticles was proposed. Comparison of mono- and bimetallic nanocatalysts in the ESR reaction was carried out. IR-PAN-Co-Ru catalyst provided a hydrogen yield of 5.6 mole per mole of EtOH.